2017
DOI: 10.1016/j.jtumed.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Cadaver dissection: A positive experience among Saudi female medical students

Abstract: Objectives The objectives of this study were to evaluate first-year undergraduate female preclinical medical students' behaviours, experiences, and emotions regarding cadaver dissection. The evaluation was performed during the 2013–2014 academic year, six months after starting the dissection course. Methods A 14-statement questionnaire was administered to a group of 200 first-year undergraduate female preclinical medical students at the College of Medicine, King Abdulaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
11
1
1
Order By: Relevance
“…90% of the participants disagreed on comparative usefulness of these modalities. This result was contradictory to the findings documented by Rajeh NA et al, 20 who reported only 59% of the student not in favor of using newer technologies.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…90% of the participants disagreed on comparative usefulness of these modalities. This result was contradictory to the findings documented by Rajeh NA et al, 20 who reported only 59% of the student not in favor of using newer technologies.…”
Section: Discussioncontrasting
confidence: 92%
“…Indeed, prosected specimen would not give the similar orientation as the firsthand experience of cadaveric dissection. Agnihotri & Sagoo et al 14 and Rajeh NA et al 20 reported the similar opinion to be 83.66% and 81% respectively. Similar observation was seen for the opinion of participants about the usage of alternative teaching methodology like plastic models, plastinated specimens and virtual reality based learning for studying human anatomy.…”
Section: Discussionmentioning
confidence: 77%
“…The ethical acceptability of cadaver dissection as agreed by most students irrespective of religion indicates that cadaver is a valuable gift to medical education. This is supported by the findings of Agnihotri and Sagoo [15] and Rajeh et al [16] Our students agreed that cadaver dissection should not be replaced with plastic models or 3D images (75.6%) and is the best method of learning anatomy (95.1%). Self or instructor assisted dissection was preferred by 92.7% of our respondents to studying prosect-ed specimen or dissected cadaver.…”
Section: Discussionsupporting
confidence: 83%
“…A question in the study of Agnihotri and Sagoo from the research publications we investigated the ethical acceptability of the cadaveric dissection, and a similar question was also investigated in the Rajeh et al (11,12).…”
Section: Discussionmentioning
confidence: 99%